Methodology for the Design and Evaluation of Green Roofs in Egypt - Mostafa El-Ahwal; ashraf elmokadem; Naglaa Megahed; Dalia EL-Gheznawy (Port Said Engineering Research Journal, 2016)
Green roofs have been gaining popularity in recent years, as an effective way to solve many environmental problems, many countries concerned with the application of green roofs in cities. In spite of the importance of using green roofs on buildings, the use of green roofs in Egypt is still absent. Egypt has been suffering recently from increasing energy demand compared to production rates, especially in the residential sector as a result of high population growth and high temperatures. Where the main objective of the study is to reduce energy consumption, reduce carbon dioxide emissions and increase the insulation on the roofs of residential buildings, this paper is working to try applying green roofs on residential buildings in Egypt through a proposed methodology for the design and evaluation. In this context, uses and applies different sections of green roofs on residential buildings in eight climate zones of Egypt in accordance with the requirements of thermal performance of the Egyptian energy code